Pengaruh Penalaran Moral dan Sensitivitas Etika Terhadap Persepsi Etis dengan Gender Sebagai Variabel Moderasi - Theresia Joycelin Jasmine; Clara Susilawati (Universitas Katolik Soegijapranata Semarang, 2019)
Accounting profession is required to provide true financial information and give confidence to users of financial information. However, many accounting scandals eroded people trust in the accounting profession. Therefore, it is important for prospective accountants to have understanding and knowledge in regard with ethical and moral values. This study examine moderating effect of gender on the the relationship between moral reasoning and ethical perceptions and between ethical sensitivity and ethical perceptions. If accounting students have higher moral reasoning dan ethical sensitivity, the ethical perceptions of accounting students are also predicted to be higher. This study examines moral reasoning and ethical sensitivity to ethical perceptions of accounting students with gender as a moderating variabel using a sample of students from 13 universities in Semarang. This study uses simple regression analysis and moderating regression analysis (MRA). Results show gender effect the relationship between moral reasoning and ethical perceptions, but hass no effect on relationship between ethical sensitivity and ethical perceptions of accounting students. Abstrak Profesi akuntansi dituntut memberikan informasi keuangan yang benar dan memiliki etika sehingga memberikan kepercayaan kepada pengguna informasi keuangan. Namun, banyaknya skandal akuntansi menurunkan kepercayaan terhadap profesi akuntansi. Oleh karena itu, penting bagi calon akuntan memiliki pemahaman dan pengetahuan berperilaku berdasarkan nilai etis dan moral. Penelitian ini menguji efek moderasi gender terhadap hubungan antara penalaran moral dan persepsi etis dan hubungan antara sensitivitas etika dan persepsi etis mahasiswa akuntansi. Jika mahasiswa akuntansi memiliki penalaran moral dan sensitivitas etika yang tinggi maka persepsi etis mahasiswa akuntansi tersebut juga tinggi. Penelitian ini menggunakan sampel mahasiswa dari 13 Universitas di Semarang. Penelitian ini menggunakan analisis regresi sederhana dan moderating regression analysis (MRA). Hasil penelitian menunjukkan bahwa gender mempengaruhi hubungan antara penalaran moral dan sensitivitas etis tetapi tidak mempengaruhi hubungan antara penalaran moral dan persepsi etis mahasiswa akuntansi.